Miskin dan Kaya Dalam Injil Lukas dan Teologi Pembebasan - Vasika Hananti; Bambang Subandrijo (Sekolah Tinggi Teologi Sriwijaya, 2021)
Abstract: Harvey J. Sindima observed Liberation Theology as it flourished in Latin America, Africa, Asia, and the United States. The social situation in that society has some similarities in Luke's community. According to Philip Francis Esler's research, Luke's theology seeks to answer the social situation in Luke's community, especially regarding the relationship between the rich and the poor. This study aims to review Sindima's review of Liberation Theology based on Philip Francis Esler's thoughts on the relationship between rich and poor in Luke's Gospel. In Sindima's writings, the involvement of the rich has not been found as an effort to minimize the suffering of the poor. In this study, the author uses an analytical method. The result is that the good news for the poor in Liberation Theology is in line with the good news in Luke's Gospel. Moreover, in Luke's Gospel the liberation of the poor is not only the responsibility of the poor themselves as in the Theology of Liberation in Sindima's description, but also the responsibility of the rich as part of a sharing community. Abstrak: Harvey J. Sindima mengamati Teologi Pembebasan yang berkembang di Amerika Latin, Afrika, Asia, dan Amerika Serikat. Situasi sosial dalam masyarakat tersebut memiliki beberapa kesamaan dalam komunitas Lukas. Menurut penelitian Philip Francis Esler, teologi Lukas berupaya menjawab situasi sosial dalam komunitas Lukas, terutama menyangkut hubungan orang kaya dan orang miskin. Penelitian ini bertujuan untuk meninjau uraian Sindima tentang Teologi Pembebasan berdasarkan pemikiran Philip Francis Esler berkenaan dengan hubungan orang miskin dan kaya dalam Injil Lukas. Dalam tulisan Sindima masih belum ditemukan keterlibatan orang kaya sebagai upaya meminimalisir penderitaan orang miskin. Dalam penelitian ini, penulis menggunakan metode analitis. Hasil tinjauan ini adalah bahwa kabar baik bagi orang miskin dalam Teologi Pembebasan sejalan dengan pemberitaan kabar baik dalam Injil Lukas. Lebih dari itu, dalam Injil Lukas pembebasan terhadap orang miskin bukan hanya menjadi tanggung jawab orang miskin itu sendiri sebagaimana dalam Teologi Pembebasan dalam uraian Sindima, tetapi juga merupakan tanggung jawab orang kaya sebagai bagian dari komunitas yang saling berbagi.